USIA REMAJA MELAKUKAN INISIASI HUBUNGAN SEKS PRANIKAH DAN PENGGUNAAN KONTRASEPSI DI BALI - Ni Komang Yuni Rahyani (Poltekkes Kemenkes Jakarta III, 2014)
Adolescent were sexually active, will facing the negative impact in their health in the future. The study aim is to analyze the time of premarital sexual intercourse initiation and contraception use among adolescent age 15 - 18 years old in Bali. The study design was a longitudinal study with observations over 16 months. The study population was students in two high school grade 10 and 11 in the city of Denpasar. Samples were 169 respondents included in this study. Statistical analysis used the Kaplan-Meier life table to determine the premarital sexual intercourse initiation probability by age. Results: Of the 169 adolescent samples classified as not at risk (48 males and 129 females), the incidence of premarital sexual intercourse initiation in male and female was 14.6% and 6.6%, respectively. Kaplan-Meier life table analysis show that the risk of adolescent male of losing their virginity until the age of 18.5 was four times higher than female (58.5% vs. 14.2%). Contraception use were lower among female adolescent than male adolescent (37.5% vs 42.9%), and adolescent who were lived in urban area than rural area (38,5% vs 50,0%). Conclusion: Contraception use among female adolescent was lower than male adolescent. We need to improve adolescent knowledge about contraception and consideration about contraception service among adolescent who were sexually active.